Performing Objects and Theatrical Things - Schweitzer, Marlis. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book rethinks historical and contemporary theatre, performance, and cultural events by scrutinizing and theorizing the objects and things that activate stages, venues, environments, and archives.